Electoral Process and Neo-Patrimonialism: An Appraisal of Quality of Governance in Democratic Nigeria (Global Journal of Human-Social Science, 2016)
Since the restoration of democratic governance which heralded the Fourth Republic in 1999, the hopes and aspirations of the citizens for improved dividends of democracy for their material wellbeing have been truncated. This has given way to disillusionment and appalling state of living of the majority of the populace. The dwindling quality of government is not unconnected with influence of neo-patrimonial network and fraudulent electoral process. The electoral heist, which robs the political elites the muchneeded legitimacy makes them, creates an amalgam of political network amongst major power merchants within the country for regime stability and political survival. The ruling elites are therefore not answerable to the citizens but to this network to the detriment of the common man. This work appraises the democratic governance in the country since the military disengaged from the nation's politics in 1999; it argues that the nature of Nigeria's electoral process and neo-patrimonial network ultimately result in the low quality of government. Credible electoral process is not only sine qua non for standard democratic governance but also a crucial element for the realisation of the much-desired dividends of democracy for the citizens.
Keywords: clientelism; electoral process; electoral good governance; legitimacy; neo-patrimonialism